Efficacy, safety and tolerability of formula-based unilateral vs bilateral electroconvulsive therapy in the treatment of major depression: A randomized open label controlled trial. (January 2021) - Dominiak, Monika; Antosik-Wójcińska, Anna Z.; Goetz, Zuzanna; Sikorska, Olga; Stefanowski, Bogdan; Gorostiza, Dagny; Święcicki, Łukasz
Abstract: Electroconvulsive therapy (ECT) remains the most effective treatment of depression, though it is still unclear which of its type is the most beneficial. The aim of this study was to compare the formula-based right unilateral ECT (RUL) with the fronto-temporal bilateral ECT (BT), in terms of their efficacy, safety and tolerability in patients with bipolar or unipolar depression. Ninety-one patients were randomly assigned to either BT (n = 45) or RUL (n = 46) ECT. Brief pulse width (0.5 ms) and a formula-based dosing method were applied. The clinical efficacy was assessed using the Hamilton Depression Rating Scale (HDRS-21).The somatic state was monitored throughout the ECT course and cognitive examination included: general cognitive performance, executive functions, visual-spatial functions, verbal fluency, verbal memory and autobiographical memory. Efficacy outcomes were not found to be significantly different between groups when using higher doses of energy in RUL ECT. Patients in RUL group were less likely to be confused and experienced increased blood pressure. The indices of general cognitive performance and verbal auditory memory were also significantly better this group, while BT ECT did not change these functions. Both ECT types resulted in a decline in the retrieval consistency of autobiographical memory that persists for at least three months and was significantly more marked in BT group as compared to RUL. In conclusion, formula-based RUL ECT does not differ from BT in antidepressant efficacy and has an advantage in terms of safety (lower incidence of increased blood pressure and fewer disturbances of consciousness) and tolerability (impact on cognitive functions). Highlights: Formula-based unilateral (RUL) ECT was equally effective as bilateral (BT) ECT. To achieve similar efficacy higher energy doses in RUL than in BT ECT were required. Delirium and increased blood pressure were less frequent in RUL ECT. RUL ECT had an advantage in terms of tolerability (impact on cognitive functions). Decline in retrieval consistency of autobiographical memory was greater in BT ECT.